Pleistocene Lacustrine Deposits and Molluscan Paleontology of Western Ohio, Eastern Indiana and Southern Michigan - Mark J. Camp (Hello World!, 1973)
A paleoecologic study of Late Wisconsin lacustrine deposits at Castalia Prairie, Rushcreek Lake, and Silver Lake in Ohio; Fourmile Lake in Michigan; and Big Turkey Lake and Wabee Lake in Indiana, using short stratigraphic sections, revealed that contained molluscan faunas were similar in composition. Amnicola limosa, A. lustrica, Valvata tricarinata, Gyraulus parvus, Helisoma anceps striatum, Physa gyrina hildrethiana, and Sphaeriidae occurred in each of the deposits with the exception of Castalia Prairie. The latter lacked members of the Amnicolidae and Valvatidae, families which require permanent water bodies. The Castalia Prairie deposit is thought to have consisted of shallow temporary lakes fed by springs. The other lacustrine deposits were formed in typical permanent marl lakes. Amnicola lustrica and Helisoma anceps no longer live in Ohio, Indiana, and southern Michigan lakes because with the retreat of glacier ice northward, water temperatures rose, forcing organisms that preferred cooler water to migrate northward into Wissconsin, Minnesota, northern Michigan, and Canada. Gyraulus parvus was the most significant mollusk, occurring in large numbers in each deposit. Goniobasis livescens was common only in the Wabee Lake deposit, where it occurred in oncolites. Pomatiopsis lapidaria was found only in the Castalia Prairie section, recording the presence of flowing water, probably from springs.